Phylogeny of sea spiders (Arthropoda: Pycnogonida) inferred from mitochondrial genome and 18S ribosomal RNA gene sequences - Sabroux, Romain; Corbari, Laure; Hassanin, Alexandre (Molecular phylogenetics and evolution, 2023)
[Display omitted] •152 mitogenomes and 120 18S ribosomal genes of sea spiders were sequenced.•Phylogenetic signal extraction is impacted when high levels of missing data are included.•Strong support for four superfamilies, six families, four subfamilies.•Most cephalic appendage characters have evolved by convergence in different families.•Poorly resolved deep relationships may be due to radiation before Jurassic. The phylogeny of sea spiders has been debated for more than a century. Despite several molecular studies in the last twenty years, interfamilial relationships remain uncertain. In the present study, relationships within Pycnogonida are examined in the light of a new dataset composed of 160 mitochondrial genomes (including 152 new sequences) and 130 18S rRNA gene sequences (including 120 new sequences), from 141 sea spider morphospecies representing 26 genera and 9 families. Node congruence between mitochondrial and nuclear markers was analysed to identify the most reliable relationships. We also reanalysed a multilocus dataset previously published and showed that the high percentages of missing data make phylogenetic conclusions difficult and uncertain. Our results support the monophyly of most families currently accepted, except Callipallenidae and Nymphonidae, the monophyly of the superfamilies Ammotheoidea (Ammotheidae + Pallenopsidae), Nymphonoidea (Nymphonidae + Callipallenidae), Phoxichilidioidea (Phoxichilidiidae + Endeidae) and Colossendeoidea (Colossendeidae + Pycnogonidae + Rhynchothoracidae), and the sister-group relationship between Ammotheoidea and Phoxichilidioidea. We discuss the morphological evolution of sea spiders, identifying homoplastic characters and possible synapomorphies. We also discuss the palaeontological and phylogenetic arguments supporting either a radiation of sea spiders prior to Jurassic or a progressive diversification from Ordovician or Cambrian.